Family mismanagement and the repercussions on the society: an Islamic shar’i of effacing the menace - Kumo, Aishatu Abubakar; Zakariyah, Luqman; Haneef, Sayed Sikandar Shah (2017)
From the Islamic point of view, firmly rooting the Islamic principles of family make the social structure of the society become solidified. But when the unified bond becomes watery, the society begins to tumble. The glaring western system has encroached into the Muslims family whereby the actual Islamic practices of handling the family is neglected. The objectives stipulated by the creator for the wellbeing of the individual is the family, based upon the relationship between a man and a woman. The concept of good governance is in discharging trust and justice, accountability and transparency. The duties of spouse toward each other and their children should be discharge diligently. The advocates for progress of women is directly linked to social justice and progress on one hand, while disastrous to the family on the other hand. Thus, the social advancement of women cannot be at the detriment of the husband and the children. The contemporary world is witnessing a changing of roles within the family where the weaker sex is exposed to being the bread winner of the family. Islam is not against economic progress of women, but the exchange in duties, or over-burdening the women with more responsibilities will lead to disruptions, inefficiency and rejection of the natural distributions of labor. Therefore, As Muslim Ummah is characterized with the quality of being ‘moderate’ or justly balanced, the desire for worldly pursue and ‘modernity’ or ‘progressiveness’ should not be the priority of any Muslim, neither should the gold without glitter of the non-Muslims attract or distract the Muslim from the specious diamond at his disposal